Diagnostic accuracy of specific IgE antibodies measurements in occupational airway allergy to high molecular weight agents - Joanna Zgorzelska-Kowalik; Jolanta Walusiak-Skorupa; Ewa Nowakowska-Świrta; Marta Wiszniewska (Nofer Institute of Occupational Medicine, 2017)
Background: The performance of specific inhalation challenge test (SICT) - reference method in diagnostics of occupational allergy - has some limitations due to health status of a particular patient. Therefore, it is extremely important to identify usefulness of other tests, and the evaluation of diagnostic accuracy of commercially available serum specific immunoglobulin E (sIgE) kits to the most common high molecular weight agents has been launched. Material and Methods: The study group comprised 141 subjects - 110 bakers and 31 farmers - with suspicion of occupational airway allergy. All patients underwent evaluation of serum sIgE to occupational allergens with the use of Phadia and Allergopharma kits: in bakers to flour mix and α-amylase, in farmers to epithelium of cow, pig and feathers. Specific inhalation challenge test with workplace allergens performed in all subjects was a reference method for further analysis. Results: Serum specific IgE to flour mix had the highest sensitivity (Phadia - 95.6%, Allergopharma - 88.3%), while its specificity was relatively low (Phadia - 47.8%, Allergopharma - 25%). There were numerous discrepancies between the results of sIgE estimation for particular single allergens (k87, e4, e83), as well as for their mixtures (fx901, fx20, ex71), performed with the kits of both companies (Phadia vs. Allergopharma). Conclusions: Evaluation of serum specific IgE is characterized by inadequate sensitivity, specificity and predictive value to take the place of specific inhalation challenge test in diagnostics of occupational respiratory allergy. Med Pr 2017;68(1):31-43